NDR-21 (Neuroplastic Dopamine Reset): Model Intervensi Berbasis Sekolah untuk Memulihkan Regulasi Perhatian dan Sistem Penghargaan pada Remaja - M. Osama Ergi Setiawan; Nasywa Fitri Adelia (Faculty of Social and Political Science, 2026)
The rapid expansion of digital technologies, particularly short-form video platforms, has fundamentally reshaped adolescents’ cognitive and behavioral landscapes. Continuous exposure to high-frequency, instant-reward stimuli has been associated with fragmented attention, diminished tolerance for cognitively demanding tasks, and weakened executive control. While existing interventions such as digital literacy programs, screen-time restrictions, and individual digital detox initiatives—have sought to mitigate these challenges, they often emphasize behavioral awareness without systematically incorporating principles of neuroplasticity and dopaminergic reward regulation. This article introduces the NDR-21 (Neuroplastic Dopamine Reset) model, a structured 21-day school-based intervention designed to recalibrate the reward system and enhance sustained attention among students aged 12–18 years. Drawing upon interdisciplinary insights from developmental neuroscience, educational psychology, and behavioral science, the model is organized into three progressive phases: stimulus stabilization (Days 1–7), cognitive endurance (Days 8–14), and consolidation and evaluation (Days 15–21). The article outlines the theoretical foundations of the intervention, its operational design, and a proposed quasi-experimental framework for empirical validation. Anticipated outcomes include an increase in distraction-free focus duration, a reduction in executive interference as measured by the Stroop Color–Word Test, and a decrease in daily screen time. By translating neuroscientific evidence into a feasible educational protocol, the NDR-21 model offers a preventive and scalable strategy to strengthen adolescents’ cognitive resilience and support the development of human capital in the context of Indonesia’s demographic transition. The study contributes to the growing discourse on the integration of neuroscience-informed approaches within educational policy and practice, emphasizing the importance of systemic, evidence-based interventions in addressing the neurobehavioral consequences of digital overstimulation.